Metode Penelitian dan Pemahaman Hadis Musykil - Abd Wahid (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
It is said hadis musykil (dubious hadith) due to two main factors; difficulty in understanding its content and its contradictory to the other hadiths or the Qur’an. This kind of hadith has no problem with its sanad (narrators) to regard it as valid hadith, sahih hadith. For this reason, the muhaddithin ulamas make serious efforts to understand this kind of hadith. They also set theories and methods to solve problems related to musykil hadith. Their efforts now become one branch of ulum al-hadith so called al-`ilm musykil al-hadith.